The effect of short-term and long-term application of fisetin on experimentally induced airway hyperreactivity - Kazimierová I.; Pappová L.; Šútovská M.; Fraňová S. (Sciendo, 2017)
Background: Fisetin, a derivate from the flavonol group may possess a variety of pharmacological effects. The aim of the presented study was to evaluate the bronchodilatory effect of fisetin after the acute or the chronic administration to guinea pigs with allergic airway inflammation.